2008
DOI: 10.1007/s11060-008-9769-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of patients who may benefit from the prophylactic cranial radiotherapy among breast cancer patients with brain metastasis

Abstract: Since there is a tendency to early brain metastasis in early stage patients with high-grade, lobular/mixed type histology tumors and with a high number of involved lymph nodes, the value of PCI can be explored in these patients by a well designed prospective trial. Advanced stage chemosensitive patients with ErbB-2 over-expression and/or with hepatic metastasis at their first relapse may be candidates for PCI. There is no place for PCI in chemoresistant and triple-negative breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 28 publications
4
28
1
Order By: Relevance
“…Patients with TNC in our study also had 1.8 times more risk of developing brain metastasis. It had been reported that TNC patients had shorter survival after diagnosing brain metastasis when compared to non TNC counterparts and hence is a poor prognostic indicator (Saip et al, 2009). Consistent with findings reported in Western population (Rodriguez-Pinilla et al, 2006;Dent et al, 2009), we did not find any difference between the TNC and non TNC groups in incidence of bone metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with TNC in our study also had 1.8 times more risk of developing brain metastasis. It had been reported that TNC patients had shorter survival after diagnosing brain metastasis when compared to non TNC counterparts and hence is a poor prognostic indicator (Saip et al, 2009). Consistent with findings reported in Western population (Rodriguez-Pinilla et al, 2006;Dent et al, 2009), we did not find any difference between the TNC and non TNC groups in incidence of bone metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…Once brain metastases are diagnosed the survival is usually poor. Reported median survival rates of breast cancer patients with brain metastasis are usually in the range of 3 to 8 months [9,14,16,17,32]. Prophylactic cranial irradiation has been shown to effectively reduce the frequency of brain metastases and to improve the survival in lung cancer [33-35].…”
Section: Discussionmentioning
confidence: 99%
“…A number of patient and tumor characteristics, including younger age (premenopausal or \50 years) [17], the presence of lung or liver metastases [17], negative hormonereceptor (HR) status [18], larger tumor size [19,20], larger number of involved lymph nodes [20,21], and positivity for human epidermal growth factor receptor 2 (HER2) [19,22], have been identified as risk factors for developing BM [18,20,21,[23][24][25]. Regarding the relationship between HER2 status and the incidence of BM, patients with HER2-positive breast cancer are at risk of developing BM, with cumulative incidence as high as 30-50% [17,22,24,26,27].…”
Section: Risk Factors Of Developing Bm Among Patients With Breast Cancermentioning
confidence: 99%